A Retrospective Survey of Childhood ADHD Symptomatology Among Adult Narcoleptics. (October 2013) - Modestino, Edward J.; Winchester, Jeanna
Objective : This study examined the retrospective history of childhood ADHD symptomatology in an adult narcoleptic population (Narcolepsy Group [NG]: n = 161) compared with a control group (CG: n = 117).Method : Both groups completed the Wender Utah Rating Scale (WURS), a retrospective self-report questionnaire indicating the presence of childhood ADHD symptomatology in adults.Results : Childhood ADHD symptoms were significantly greater in NG than CG ( p < .001). Joint prevalence calculations of childhood ADHD symptomatology in NG were more than 8 to 15 times greater than expected. Among NG, those individuals with a greater score on the WURS, indicative of childhood ADHD symptomatology, also had shorter sleep onsets on the Multiple Sleep Latency Test, a common objective measure of sleepiness, t (97) = −7.11, p < .05.Conclusion : It appears that self-reported childhood ADHD symptomatology history among adult narcoleptics is common. Future research is warranted with adult narcoleptics to elucidate the true nature of this.